The impact of BCG strains and repeat vaccinations on immunodiagnostic tests in Eurasian badgers (Meles meles). Issue 34 (12th August 2022) - Courcier, Emily A.; Collins, Shane F.; McCormick, Carl M.; Arnold, Mark E.; Corbett, David M.; Ford, Tom; McGeown, Clare F.; Barry, Claire; Kirke, Raymond; Menzies, Fraser D.
Abstract: Bacille Calmette-Guerin (BCG) is a potential tool in the control of Mycobacterium bovis in European badgers ( Meles meles) . A five year Test and Vaccinate or Remove (TVR) research intervention project commenced in 2014 using two BCG strains (BCG Copenhagen 1331 (Years 1–3/ BadgerBCG) and BCG Sofia SL2222 (Years 4–5). Badgers were recaptured around 9 weeks after the Year 5 vaccination and then again a year later. The Dual-Path Platform (DPP) Vet TB assay was used to detect serological evidence of M. bovis infection. Of the 48 badgers, 47 had increased Line 1 readings (MPB83 antigen) between the Year 5 vaccination and subsequent recapture. The number of BCG Sofia vaccinations influenced whether a badger tested positive to the recapture DPP VetTB assay Line 1 (p < 0.001) while the number of BadgerBCG vaccinations did not significantly affect recapture Line 1 results (p = 0.59). Line 1 relative light units (RLU) were more pronounced in tests run with sera than whole blood. The results from an in_house MPB83 ELISA results indicated that the WB DPP VetTB assay may not detect lower MPB83 IgG levels as well as the serum DPP VetTB assay. Changes in interferon gamma assay (IFN-γ) results were seen in 2019 with significantly increased CFP-10 and PPDB readings. Unlike BadgerBCG, BCG Sofia induces an immune response to MPB83 (the immune dominant antigen in M. bovis badger infection) that then affects the use of immunodiagnostic tests. The use of the DPP VetTB assay in recaptured BCG Sofia vaccinated badgers within the same trapping season is precluded and caution should be used in badgers vaccinated with BCG Sofia in previous years. The results suggest that the DPP VetTB assay can be used with confidence in badgers vaccinated with BadgerBCG as a single or repeated doses.